Efektivitas Pembelajaran Daring Berbasis YouTube Terhadap Kemampuan Pemecahan Masalah Matematika - Muhammad Syahril Harahap; Marzuki Ahmad; Sintiya Mayuni Lumbantobing (JURNAL MathEdu (Mathematic Education Journal), 2022)
The aim of this study is to describe the effectiveness of the application of YouTube-based online learning on the Mathematics Problem Solving Ability (MPSA) of students in class VIII-5 of SMP Negeri 4 Padangsidimpuan. This research uses descriptive quantitative method with a sample of 17 students. Data collection techniques in this study using observation and tests. Based on the results of descriptive analysis, it was found: (a) The average application of YouTube-based online learning was 3.56 with the "Very Good" category, (b) The average MPSA of students before the application of YouTube-based online learning was 55 with the "Less" category. and after the implementation of YouTube-based online learning is 95 with the category “Excellent”. Furthermore, based on inferential statistics using the t test (paired sample test) and the N-Gain formula, the results obtained show a significant value of less than 0.05 (0.000 0.05) and g = 0.90 with the "High" category. This means that the application of YouTube-based online learning is effective for the MPSA of students in grades VIII-5 of SMP Negeri 4 Padangsidimpuan.